THE INFLUENCE OF SERVICE QUALITY ON PATIENT SATISFACTION IS INTERVENTED BY TRUST IN THE SEHATI PROGRAM AT DR. H. MARSIDI JUDONO TANJUNG PANDAN BELITUNG - Aurora Oktabella Andini; Hery Winoto Tj; Soegeng Wahyoedi (RADJA PUBLIKA, 2025)
This study aims to analyze the effect of service quality on patient satisfaction, both directly and through the mediation of patient trust. The findings reveal that: (1) service quality has a significant positive effect on patient satisfaction, meaning that the better the hospital's service quality, the higher the level of patient satisfaction; (2) patient trust has a significant positive effect on patient satisfaction, indicating that increased patient trust will lead to higher satisfaction; (3) service quality has a significant positive effect on patient trust, meaning that improved hospital service quality will enhance patient trust; and (4) service quality significantly and positively affects patient satisfaction through the mediation of patient trust, implying that good service quality not only increases patient trust but also indirectly enhances patient satisfaction. This study emphasizes the importance of service quality and patient trust in improving patient satisfaction in hospitals.